Offshoring and Volatility: Evidence from Mexico's Maquiladora Industry - Bergin, Paul R; Feenstra, Robert C; Hanson, Gordon H (American Economic Review, 2009)
This paper studies the second-moment properties of offshoring, the arrangement whereby firms carry out particular stages of production abroad. It documents a new empirical regularity: maquiladora industries in Mexico that are associated with US offshoring experience fluctuations in employment that are twice as volatile as the corresponding industries in the United States. This finding is not attributable simply to higher volatility in the overall Mexican economy, nor to the smaller size of Mexico's industries compared to US counterparts. (JEL F14, F23, L24, L25, L60, O14)